Development of Quality Control Methods for Polyherbal Formulation of Mahasudarshan Churna - SHRIVASTAVA, S.; KAPOOR, S.; DUBEY, D. (Asian Journal of Chemistry, 2010)
In the present study, three batches of different marketed polyherbal formulation, Mahasudarshan churna were procured from the local market and they were evaluated as per Indian Pharmacopoeia and WHO guidelines on the following parameters viz., organoleptic characteristics, extractive value, ash value, physical characteristics, moisture content, loss on drying, phytochemical evaluation, fluorescence analysis, pH value etc. The result of the present study revealed that all three batches of Mahasudarshan churna were found in close proximity. This study on Mahasudarshan churna was precise, reproducible and may be considered as a protocol for its evaluation.